An intra-hour control strategy for aggregated electric storage space heating load. (December 2015) - Alahäivälä, Antti; Ali, Mubbashir; Lehtonen, Matti; Jokisalo, Juha
Highlights: A strategy to remove retailer's forecast errors with demand response is proposed. Studied loads are participating in a real-time price program. Simulations indicate that the strategy is able to reduce retailer's forecasting error related costs. Abstract: Forecasting errors in a power system occasionally leads to situations where either production or consumption is required to be altered. In order to improve demand-side contribution under these special conditions, this paper introduces an intra-hour control strategy that allows a retailer to request regulating power from flexible loads. The load under research is electric storage space heating (ESSH) employing model predictive control (MPC) for minimizing the heating cost and ensuring customer comfort. In the proposed framework, a regulation request is sent to the loads, after which they solve the price and volume of their regulation bids and communicate the bids back to the retailer. Centrally, the retailer aims to minimize prediction error costs by finding the cheapest mix of buying regulation from the loads and settling the error later in the imbalance settlement. The proposed control strategy is tested and evaluated in dynamic simulations. The results indicate that the thermal storages can be regulated by the proposed strategy and some savings in imbalance costs are possible.